Adverse events as potential predictive factors of therapeutic activity in patients with unresectable hepatocellular carcinoma treated with atezolizumab plus bevacizumab - Toshifumi Tada; Takashi Kumada; Atsushi Hiraoka; Masashi Hirooka; Kazuya Kariyama; Joji Tani; Masanori Atsukawa; Koichi Takaguchi; Ei Itobayashi; Shinya Fukunishi; Kunihiko Tsuji; Toru Ishikawa; et al. (Cancer Medicine, 2023)
Abstract Aim To investigate the possible correlation between the development of adverse events (AEs) and prognosis in patients with unresectable hepatocellular carcinoma (HCC) treated with atezolizumab plus bevacizumab (Atez/Bev). Methods A total of 286 patients with unresectable HCC treated with Atez/Bev as first‐line systematic therapy were included. Results Regarding treatment‐related AEs, decreased appetite of any grade, proteinuria of any grade, and fatigue of any grade were found with a frequency of ≥20%. Multivariate analysis adjusted for immune‐related liver injury, immune‐related endocrine dysfunction, proteinuria, fatigue, decreased appetite, hypertension, sex, age, Eastern Cooperative Oncology Group performance status, HCC etiology, HCC stage, Child–Pugh score, and α‐fetoprotein showed that hypertension of any grade (hazard ratio [HR], 0.527; 95% confidence interval [CI], 0.326–0.854; p = 0.009) and α‐fetoprotein ≥100 ng/ml (HR, 1.642; 95% CI, 1.111–2.427; p = 0.013) were independently associated with progression‐free survival. Multivariate analysis adjusted for the same AEs showed that fatigue (HR, 2.354; 95% CI, 1.299–4.510; p = 0.010) was independently associated with overall survival. Median progression‐free survival was 6.5 months (95% CI, 5.2–8.1) in patients without hypertension of any grade and 12.6 months (95% CI, 6.7–not available) in patients with hypertension of any grade (p = 0.035). The overall survival was significantly shorter in patients in whom treatment‐related fatigue of any grade was observed (p < 0.001). Regarding response rates, the disease control rate of patients who developed treatment‐related hypertension (94.2%) was significantly higher than those who did not (79.1%) (p = 0.009). Conclusions Treatment‐related hypertension is associated with good outcomes in patients with HCC treated with Atez/Bev.